Conceptualising women's perinatal well-being: A systematic review of theoretical discussions. (February 2020) - Wadephul, Franziska; Glover, Lesley; Jomeen, Julie
Highlights: Perinatal well-being is dynamic, complex and multi-dimensional. There is a lack of theorising about well-being, particularly in labour and birth. There is a need for a comprehensive model of perinatal well-being. Perinatal well-being does not exist in a vacuum but within a wider life context. Themes identified contribute to a tentative model of perinatal well-being. Abstract: Background: Perinatal well-being has increasingly become the focus of research, clinical practice and policy. However, attention has mostly been on a reductionist understanding of well-being based on a mind-body duality. Conceptual clarity around what constitutes well-being beyond this is lacking. Aim: To systematically review theoretical discussions of perinatal well-being in the academic literature. Design and methods: A search of online databases identified papers which discussed perinatal well-being theoretically, taking a multi-dimensional approach to well-being. Thematic synthesis was used to identify and synthesize relevant elements within the included papers. Findings: Eight papers were identified for inclusion in this review. All contributed a number of elements towards a theoretical discussion of perinatal well-being. Three themes were developed: (1) the importance of a number of general domains of women's lives and domains specific to the perinatal period, (2) well-being as a subjective and individual experience with physical/embodied, affective, and psychological/cognitive aspects, and (3) the dynamic nature of well-being. Conclusions and implications for practice: Perinatal well-being is a complex, multi-dimensional construct. Current theoretical discussions in the academic literature do not provide a comprehensive model or conceptualisation covering all aspects of well-being during the perinatal period. Further theoretical work is required, particularly with regards to theorising well-being during labour and birth, the perinatal period as a continuum, and the role played by women's expectations. The themes identified in this review contribute to a tentative model of perinatal well-being, taking note particularly of the dynamic nature of well-being. This model should be refined and validated through empirical work and can then be used to underpin further research and the development of a multi-dimensional measure of perinatal well-being.